(untitled) (Global Journal of Management and Business Research, 2023)
Since they typically live hand-to-mouth poor households are disproportionately affected by inflation Even modest price increases have a significant impact on poorer families consumption compared to wealthier families In addition unchecked inflation creates poverty traps It forces low-income families to eat lower-quality food to prevent famine which can have an impact on the cognitive development of their kids Nowadays that is a serious issue in our country so the researcher has chosen that topic The study is based on primary as well as secondary data which was collected by a convenient sampling method from 203 respondents through a structured questionnaire in Saurashtra The researcher used different tests and tools including pilot surveys a reliability test the results of which are given below and the above tools based on different objectives The researcher used the Mann Whitney U test U for Gender and Place and the Kruskal Wallis test H in other cases It is also seen that 63 of respondents say that inflation is increasing due Inflation has increased due to the current Russia-Ukraine war and at present there is a problem of inflation in most of the countries of the world because 85 of respondents agree with this sentence When there is inflation saving investment decreases because 80 of respondents agree with the following sentence additionally there is more than one reason for inflation in the current scenario because 93 of respondents agree with the following sentences and finally it can be seen that if the price of crude oil petrol diesel rises inflation will rise immediately because 80 of respondents agree From all the above sentences it is seen that the effect of inflation on the standard of living has increased because the entire item s price has increased